Clean energy nation : freeing America from the tyranny of fossil fuels - McNerney, Gerald; Cheek, Martin, 1966- (New York : AMACOM, 2012)
'Clean Energy Nation is an eye-opening look at the world's history with fossil fuels and what we must do in the next century to save our environment. With a specific focus on the current American dependence on oil, this book delivers a sobering call to action. Here, Jerry McNerney, the only United States Congressman ever to have had a career as a renewable energy engineer, and writer Martin Cheek inspire all Americans to take action to free our country from its dangerous addiction to oil and help steer us toward the goal of genuine energy independence.'--From publisher's description
Includes bibliographical references (p. 267-295) and index.
Keywords: Power resources -- United States; Renewable energy sources -- United States; Fossil fuels -- Environmental aspects -- United States; Energy policy -- United States